Literasi Informasi Siswa di Sekolah yang Memiliki dan Tidak Memiliki Pustakawan: Studi Komparatif di SMAN 1 Kubung dan SMAN 1 Junjungsirih - Fadhilah, Rahmi; Marlini, Marlini; Erlianti, Gustina (Lembaga Yasin AlSys, 2026)
This study aimed to identify differences in students’ information literacy levels between schools that have librarians and those that do not. A quantitative approach with a comparative design was employed, conducted at SMAN 1 Kubung as a school with a librarian and SMAN 1 Junjung Sirih as a school without a librarian. The research population comprised all students in both schools, with the sample determined using proportionate stratified random sampling. The research instrument was an information literacy questionnaire measuring the ability to recognise information needs, search for information, evaluate sources, and use information ethically. Data were analysed using descriptive and inferential statistics through an independent t-test to compare the information literacy levels between the two groups of students. The results showed a significant difference in students’ information literacy levels, with students in the school that has a librarian demonstrating higher levels of information literacy than those in the school without a librarian. These findings indicate that the presence of a librarian in schools plays an important role in supporting the development of students’ information literacy and is expected to serve as a consideration for schools and policymakers in improving the quality of school library services.